THE EFFECTIVENESS OF PTPN11 GENE ANALYSIS IN THE PRENATAL DIAGNOSIS OF NOONAN SYNDROME - Güven Toksoy; Fatih Tepgeç; Tuğba Saraç Sivrikoz; İbrahim Halil Kalelioğlu; Selma Demir; Recep Has; Atıl Yüksel; Zehra Oya Uyguner; Seher Başaran (İstanbul Tıp Fakültesi Dergisi)
Objective: Dominant pathogenic variants in 29 RAS-MAPK (Rat-sarcoma-Mitogen-activated-protein-kinase) pathway genes, important for the regulation of cell growth, differentiation, aging and cell-cycle, are responsible for RASopathies, Noonan syndrome (NS) is the most common form. PTPN11 variants are detected in 50% of the cases, 90% being identified in the first SH2 and in the catalytic domain at the N- and C-terminals of the peptide, respectively. Increased nuchal translucency (NT), lymphatic system anomalies (cystic hygroma, pleural effusion, ascites), cardiac anomalies, polyhydramnios, short limb and macrocephaly are the NS-associated prenatal findings. PTPN11 association is reported in 2-3% of normal karyotyped fetuses with NT and in >10% when other NS findings are included. Material and Method: PTPN11 analysis with different approaches in 246 normal karyotyped prenatal cases with NS-associated USG findings were retrospectively evaluated. The targeted PTPN11 regions in 200 and the whole gene structure of 46 cases were examined by Sanger sequencing. Results: Pathogenic variants, including two novel variants (p.P107S and p.M504T), were identified in two fetuses with isolated NT and in three fetuses with multiple USG findings, leading to a 2% of detection rate, all found in targeted exons. Two of six cases, further investigated for targets of four Rasopathy genes, had causative genes in SOS1. One of three terminated fetuses, investigated for the targeted-gene panel, had a causative gene in RAF1 genes. Both the isolated NT and multiple USG finding groups revealed an equal detection rate of 2.3%. Discussion: PTPN11 is responsible for 50% of RASopathies and 90% of the pathogenic variants are delineated in the targeted exons. The rational, cost-effective approach for the clarification of the genetic basis of RASopathies is screening the addressed exons of PTPN11 followed by the other exons and other RASopathy related genes.